Pencegahan Fraud Pada Karyawan BMT Syariah Jatim Melalui Pendekatan Pengendalian Sistem Internal Dan Kesesuaian Kompensasi Dengan Religiusitas Sebagai Variabel Moderasi - Amarta Fasa, Mochamad; Sudaryanti, Dwiyani; Hidayah, Nur (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The purpose of this research is to analyze the influence of internal system control (X1) on fraud prevention (Y), analyze the influence of compensation suitability (X2) on fraud prevention (Y), analyze the influence of religiosity (Z) which can strengthen the influence of internal system control (X1). on fraud prevention (Y), Analyzing the influence of religiosity (Z) can strengthen the influence of compensation suitability (X2) on fraud prevention (Y). The type of research used in this research is explanatory, where the influence between certain variables through hypothesis testing is explained in detail. The primary data source in this research was obtained directly from BMT Syariah East Java employees through a questionnaire containing closed statements. Researchers selected all branch office employees as members of the research population starting from branch heads, remedial officers, account officers, savings and financing account officers, along with tellers. It is the employees at the branch who are considered to be at greatest risk of fraud, because they can have direct contact with customers, both for savings and financing transactions. From research data to testing, it shows that internal system control (X1) does not have a significant negative effect on fraud (Y) in BMT Syariah East Java employees, Compensation suitability (X2) has a negative and significant effect on fraud (Y) in East Java BMT Syariah employees, Religiosity ( Z) is unable to strengthen the negative influence of internal system control (X1) on fraud (Y) on East Java BMT Syariah employees, Religiosity (Z) is unable to strengthen the negative influence of compensation suitability (X2) on fraud (Y) on East Java BMT Syariah employees.